Consumption, Man, and Gender: Historical and Philosophical Analyses (the Example of Early Soviet Society) - Скубій, Ірина; Пилипенко, Світлана (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The research is directed on the field of history of consumption’s expansion, as well as inclined to the understanding of the gender standards and models in consumption. It is based on the theoretical achievements of gender studies, philosophy and sociology of consumption. Whereas consumption is a process that is closely connected with a gender perspective, it forces to examine the issue of constructing gender by means of consumption. Thus authors used attention the cross-disciplinary methodological approach, which allows to explore the interrelations between gender and consumption. It has been considered the way of construction feminity and masculinity in the everyday practices, as well as the formation of gender models and standards in consumption irrespectively of the career level or material status of the research actors. The case study of this article are the construction of feminity and masculinity in the everyday consumer practices in the early Soviet society, which allows to “open” the new faces of Soviet social history – consumers. Making historical analogies provides opportunity for a critical understanding of the Soviet ideological project devoted to the constructing of a "new Soviet man" and "new Soviet consumer". Despite the proclaimed principle of gender equality by the Bolshevik authorities, these changes did not significantly transform the everyday consumer practices, because in the sphere of domestic consumption most of the functions were still performed by women. However, the development of consumption had influenced the emergence of gender ideology, which resulted in expanding the opportunities for women to work in the sphere of production and distribution of consumer goods and services, as well as intensified their political participation.